Humidity and Temperature Monitoring System - A Balamurali, Sandeep P, R Siva Sandeep Reddy, R Sai Kiran (International Journal of Control and Automation, 2020)
As climatic conditions turning into a major worry among the environmentalists a gadget that can view temperature and humidity changes in the earth is required. The main objective of the project is to build up an electronic device that can detect the temperature and humidity changes and send the information to the cloud for analysis. We use DHT11 sensor for sending temperature and humidity data to THINGSPEAK using ARDUINO Uno and ESP8266 module. This project was divided into two sections that include hardware and software. The hardware part involved is building the temperature sensor connected to ARDUINO board and for the software part involved is written programming in ARDUINO IDE. The data is carried over the internet using THINGSPEAK IoT server and this information can be accessed through applications and further moves can be made. The proposed system has an advantage of high accuracy transmission, complex use of traditional system with the analog DHT11 sensor and makes measurement for temperature and humidity with high precision. The measurement and monitoring are vital in this competitive era of innovations.